2022
DOI: 10.1128/aem.01818-21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Bacterial Diversity and Mucosome Function Differentiate Susceptibility of Appalachian Salamanders to Chytrid Fungal Infection

Abstract: How host mucosal defenses interact, and influence disease outcome is critical in understanding host defenses against pathogens. A more detailed understanding is needed of the interactions between the host and the functioning of its mucosal defenses in pathogen defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…These differences could be explained by differences in skin mucus composition, immune response, or gene expression before and after metamorphosis as it has been proposed that mucus chemical composition (e.g., production of antimicrobial peptides) play a critical role in shaping the skin microbiota as well as in defense against pathogens [ 30 , 54 , 55 ]. Antimicrobial peptide repertory of the skin changes through development in some frog species [ 56 ], and some bacteria can induce the synthesis of specific antimicrobial peptides [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences could be explained by differences in skin mucus composition, immune response, or gene expression before and after metamorphosis as it has been proposed that mucus chemical composition (e.g., production of antimicrobial peptides) play a critical role in shaping the skin microbiota as well as in defense against pathogens [ 30 , 54 , 55 ]. Antimicrobial peptide repertory of the skin changes through development in some frog species [ 56 ], and some bacteria can induce the synthesis of specific antimicrobial peptides [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observations in several amphibian species indicate that certain bacteria with properties such as biofilm formation [ 82 ] or putative inhibitory ability [ 55 ] are positively or negatively corelated with a decrease of Bd prevalence. Thus, we expect that bacteria with negative correlations to infection intensity could be important in the defense against Bd in A. altamirani .…”
Section: Discussionmentioning
confidence: 99%
“…Open Sci. 10: 220810 [141], our results suggest that despite containing many putative anti-Bd skin microbes, the pre-existing skin microbiome is not a key factor accounting for control of Bd infection in hellbenders.…”
Section: Microbiome Response To Experimental Vaccination and Challengementioning
confidence: 77%
“…Our use of microbiome read counts to test for a relationship between Bd -inhibitory bacteria and Bd produced comparable results to studies which used quantitative PCR to detect and quantify the abundance of Bd . For example, Jiménez et al (2022) found that Bd infection intensity significantly decreased on the skin of the eastern newt ( Notophthalmus viridescens ) as the relative abundance of putative Bd -inhibitory bacteria increased. Similarly, Flechas et al (2019) found lower Bd infection prevalence within post-metamorphic life stages which also had high relative abundances of Bd -inhibitory bacteria in two frog species.…”
Section: Discussionmentioning
confidence: 99%